Shifting paradigms Mexico in color: Ellen Auerbach’s exile photography (Itinera, 2022)
In 1955, Ellen Auerbach, a Weimarian advertising photographer of the Bauhaus circles, chose to document her trip to Mexico with her colleague Eliot Porter, using color photography for the first time in her career.This article seeks to contextualize, for the first time, Auerbach’s decision to use color in her work – and within the history of modernism in general. In a discourse where exile studies interweave closely with art theory, I intend to trace the paths of a modernism that might have been, but that was erased by history and migration, demonstrating how the use of color in a non-Western exile context became a starting point for rethinking the aims and epistemic possibilities of the photographic medium within and beyond the modernist perspective.